Exporting protection: EU trade agreements, geographical indications, and gastronationalism - Martijn Huysmans (Utrecht University, Utrecht University School of Economics (U.S.E.), 2019)
A key objective of EU trade policy is to obtain wider protection for its regional specialty foods, known as Geographical Indications (GIs). While the WTO imposes a minimum level of protection, the EU has successfully considered additional protection for its GIs a red line in recent trade agreements. In the EU, trade agreements are negotiated by the Commission but require member state approval. Both Greece and Italy have threatened not to ratify CETA over insufficient GI protection, so GIs clearly matter. This article provides and analyzes new data on GI protection in 11 recent EU trade agreements. It finds that EU trade agreements are more likely to protect GIs with higher sales values and from countries in the South of Europe, where GIs are highly salient because of gastronationalism. These findings illustrate how economic considerations and political mechanisms shape and enable EU policy exports
Keywords: 330; Trade agreements; Geographical Indications; Intellectual Property; TRIPS; European Union